1994
DOI: 10.1111/j.1467-9450.1994.tb00940.x
|View full text |Cite
|
Sign up to set email alerts
|

A re‐evaluation of the psychometric properties of the Basic Character Inventory

Abstract: The aim of this study was to re‐evaluate the psychometric properties of the Basic Character Inventory (BCI). In a rather large sample of 503 subjects (323 women and 180 men, 88 non‐psychotic psychiatric inpatients and 415 non‐patients) factor analysis resulted in three factors with personality traits almost identical with the BCI Oral, Obsessive and Hysterical scales. BCI seems to be a fruitful and reliable assessment instrument for personality traits and character types as outlined in psychoanalytic theory. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…Most subscales had adequate, good, or excellent reliabilities, though Severe Superego and Imagination had reliability values below 0.70. This finding replicates the Kaldestad's (1994) study that also found poor reliability for these subscales. Therefore, the Severe Superego and Imagination subscales should be used cautiously, if at all, in future research.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Most subscales had adequate, good, or excellent reliabilities, though Severe Superego and Imagination had reliability values below 0.70. This finding replicates the Kaldestad's (1994) study that also found poor reliability for these subscales. Therefore, the Severe Superego and Imagination subscales should be used cautiously, if at all, in future research.…”
Section: Resultssupporting
confidence: 91%
“…Corroborating the findings of Kaldestad (1994), the Severe Superego and Imagination subscales from Torgersen's original BCI failed to exhibit strong reliability and should thus be used cautiously, if at all. The reliability value for Rigidity in the reduced form is somewhat weak, as well.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations